Peningkatan Kemampuan Masyarakat Desa Lero Tatari Terhadap Pemberian Pertolongan pada Kejadian Kedaruratan Pesisir Pantai - Ismunandar Ismunandar; Irsanty Collein; Fitria Masulili; Waode Fitrah Sari; Aditya Pratama; Akbar Hidayatullah (Poltekita: Jurnal Pengabdian Masyarakat, 2025)
Lero Tatari Village is an area that has a high level of vulnerability to emergencies in coastal communities because of its location on the coast, some of the people work as fishermen and live along the coast of Lero Village, Sindue District. This activity aims to increase the ability of the Lero Tatari Village community to respond to coastal community emergencies. The method of implementing community service activities is carried out through surveys, lectures, discussions, simulations, observations, mentoring and evaluation of activities by filling in post test questionnaires. The evaluation results showed that most respondents had a good knowledge score of > 75 (76.7%) after being given counseling regarding first aid in emergencies in coastal communities. The statistical test results obtained a P value of 0.024, so it can be said that there is a significant relationship between age and respondents' knowledge with a moderate strength of relationship. The conclusion was that providing education and simulations can increase people's knowledge and abilities regarding emergency first aid.